1984
DOI: 10.1016/0169-4332(84)90003-5
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of oxygen and carbon monoxide with a carbided Ni(111) surface

Abstract: The thermal decomposition of ethylene on Ni(lll) at 250°C is shown to lead to carbon deposition on and -in a later stage -below the surface. Independent of the amount of carbon below the surface, CO is adsorbed with an isosteric heat of adsorption of 105 kJ/mol. The surface carbon reacts with oxygen at 25O'C. The reaction rate is independent of the surface carbon coverage and first order in oxygen pressure. The subsurface carbon segregates to the surface after removal of the surface carbon layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, in practice and in agreement with previous kinetic studies of coke formation, , the effect of CO 2 in eq 39 is shown to be negligible. This result can be attributed to the fact that after coke is deposited the carbon covering the surface leads to an enhanced CO adsorption in the near carbon sites . Given that eq 39 describes the rate of coke formation only after t c (when a net coke formation begins, as suggested by assumption (1)) and that CO adsorption increases considerably in the near-coke regions, the considerations leading eq 39 into eq 40 are valid.…”
Section: Kinetic Modelingmentioning
confidence: 97%
“…However, in practice and in agreement with previous kinetic studies of coke formation, , the effect of CO 2 in eq 39 is shown to be negligible. This result can be attributed to the fact that after coke is deposited the carbon covering the surface leads to an enhanced CO adsorption in the near carbon sites . Given that eq 39 describes the rate of coke formation only after t c (when a net coke formation begins, as suggested by assumption (1)) and that CO adsorption increases considerably in the near-coke regions, the considerations leading eq 39 into eq 40 are valid.…”
Section: Kinetic Modelingmentioning
confidence: 97%